Principal's strategy in improving superior education quality: a case study at muhammadiyah elementary school - Sukanti, Lina; Sutarman, Sutarman (Jurnal Konseling dan Pendidikan, 2025)
This study aims to analyze strategies to improve the quality of education, analyze the external and internal environment, coordinate with the principal. This research method uses a qualitative approach, through interviews with key informants, observations of actual events, analyzing documentation. The results of the study indicate that the principal's strategy in improving the quality of education includes: 1) Planning is the process of setting organizational goals, developing strategies to achieve those goals, and making action plans that support the achievement of those organizational goals 2) Strategy implementation is the phase where management translates strategic plans and policies into real actions through program development, budgeting, and procedures 3) Evaluation is a series of activities designed to measure the success of a program. In management, expertise is needed to manage and control various elements of the organization in order to achieve the desired goals. 4) The obstacles faced are human error, lack of infrastructure.